2007
DOI: 10.1186/1471-2407-7-155
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal permeability in ovarian cancer and breast cancer patients treated with paclitaxel and platinum

Abstract: Background: Combination of platinum derivatives with paclitaxel is currently the standard front line regimen for patients with epithelial ovarian carcinoma, and represents also an active regimen in patients with metastatic breast or unknown primary carcinomas. Measurement of intestinal permeability represents one of the potential methods of noninvasive laboratory assessment of gastrointestinal mucositis induced by chemotherapy, but little is known about intestinal permeability in patients treated with paclitax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Therefore, this method may not be used to assess intestinal permeability in the colon, and the results may be invalidated by significant bacterial overgrowth in the small intestine. Although this situation may be in some instances an oversimplification, intestinal permeability is thought to represent a passive process of diffusion across 48 Gastrointestinal symptoms the mucosa. Although only nonmetabolized sugars are used to assess the intestinal permeability in the small intestine, the degradation of sucrose in the small intestine may be exploited for the use of this marker to assess the permeability of the stomach mucosa [12].…”
Section: Intestinal Permeability: Theory and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this method may not be used to assess intestinal permeability in the colon, and the results may be invalidated by significant bacterial overgrowth in the small intestine. Although this situation may be in some instances an oversimplification, intestinal permeability is thought to represent a passive process of diffusion across 48 Gastrointestinal symptoms the mucosa. Although only nonmetabolized sugars are used to assess the intestinal permeability in the small intestine, the degradation of sucrose in the small intestine may be exploited for the use of this marker to assess the permeability of the stomach mucosa [12].…”
Section: Intestinal Permeability: Theory and Methodsmentioning
confidence: 99%
“…An increase of lactulose/mannitol ratio has been described after treatment with gefitinib, an oral agent targeting epidermal growth factor receptor [52 ]. In some studies, changes of intestinal permeability have been accompanied by increased sucrose/mannitol ratio indicating associated disturbance of the permeability of gastric mucosa [48].…”
Section: Intestinal Permeability Studies In Cancer Patientsmentioning
confidence: 99%
“…An increased disaccharide/monosaccharide ratio and decreased xylose absorption have been described in experimental animal models [6] and patients with GI cancer [7] treated with different cytotoxic agents [8]. Notwithstanding, there is still much to learn about the occurrence of chemotherapy-induced alterations for extra-GI neoplasms [9] and in particular with recent FEC60 regimen (fluorouracil, epirubicin, and cyclophosphamide) [10]. Furthermore, the mechanisms underlying these alterations in neoplastic patients are not fully elucidated, since there is still a lack of information concerning all of the players actively implicated in the regulation of intestinal barrier function.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we have demonstrated that increased lactulose/mannitol ratio may predict the toxicity of cytotoxic chemotherapy (9). The measurement of gastrointestinal permeability could thus represent a useful laboratory method for follow up of cancer patients.…”
Section: Resultsmentioning
confidence: 99%